AIDS Inside and Out: HIV/AIDS and Penal Policy in Ireland and England & Wales in the 1980s and 1990s. (25th October 2018) - Weston, Janet; Berridge, Virginia
Summary: As HIV/AIDS emerged in the 1980s as a new and seemingly overwhelming public health challenge, prisons were highlighted as an important location for the control of the epidemic. Yet, they often seemed unwilling or unable to adopt national guidelines. This article compares the policy decisions made by the prison services of the Republic of Ireland and England & Wales in response to HIV/AIDS in the 1980s and 1990s, bringing together the histories of penal policy and HIV/AIDS for the first time. It develops our understanding of contemporary policy history, and demonstrates the value of a comparative approach to both penal and health histories. Policy-making was shaped by both national and more localised traditions and trends, from attitudes to criminal justice and responses to HIV/AIDS at the national level, to the histories, structures, and staffing of prison services themselves.